Phase I dose escalation study of pemetrexed and concurrent thoracic radiation in elderly patients with non-squamous non–small-cell lung cancer. (29th November 2018) - Kaira, Kyoichi; Ono, Akihiro; Kamide, Yosuke; Sunaga, Noriaki; Koga, Yasuhiko; Saitoh, Jun-ichi; Shirai, Katsuyuki; Ebara, Takeshi; Hisada, Takeshi; Ishizuka, Tamotsu
Abstract: The aim of our study was to determine the maximum tolerated dose (MTD) and recommended dose of pemetrexed with concurrent thoracic radiation therapy for elderly patients with previously untreated locally advanced non-squamous non–small-cell lung cancer (NSCLC). Pemetrexed was administered intravenously on Days 1, 22, 43, 64, 85 and 106. The initial doses of pemetrexed were planned as follows: Level 1 (400 mg/m 2 ) and Level 2 (500 mg/m 2 ). Concurrent thoracic radiation therapy was administered in 2-Gy fractions five times weekly, to a total of 60 Gy. Six patients were enrolled in the current study. The full thoracic radiotherapy dose (60 Gy) was administered for all patients. The full number of cycles (6 cycles) of chemotherapy, including induction and consolidation phases, were administered to 4 of 6 (66%) patients. At Level 1 and Level 2, none experienced a dose-limiting toxicity (DLT). There were no severe toxicities such as pulmonary toxicities, treatment-related death or Grade 2 or more radiation pneumonitis. Therefore, Level 2 was considered the MTD and was also defined as the recommended dose. An objective response was observed in 66.7% of all patients. This regimen was well tolerated and observed to be safe for the treatment of elderly patients with locally advanced non-squamous NSCLC.